2005
DOI: 10.1002/jmri.20305
|View full text |Cite
|
Sign up to set email alerts
|

Method for improving the accuracy of quantitative cerebral perfusion imaging

Abstract: Purpose:To improve the accuracy of dynamic susceptibility contrast (DSC) measurements of cerebral blood flow (CBF) and volume (CBV). Materials and Methods:In eight volunteers, steady-state CBV (CBV SS ) was measured using TrueFISP readout of inversion recovery (IR) before and after injection of a bolus of contrast. A standard DSC (STD) perfusion measurement was performed by echo-planar imaging (EPI) during passage of the bolus and subsequently used to calculate the CBF (CBF DSC ) and CBV (CBV DSC ). The ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(98 citation statements)
references
References 37 publications
(50 reference statements)
5
93
0
Order By: Relevance
“…Recently, some techniques have been derived to address quantification issues arising from AIF PVE (11,20). However, these advanced methods have not yet been widely adopted in clinical practice, in part because they are new, but also because they complicate the perfusion methodology in clinical practice and, when used individually, only address AIF PVE error, obviating the need for the extra effort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, some techniques have been derived to address quantification issues arising from AIF PVE (11,20). However, these advanced methods have not yet been widely adopted in clinical practice, in part because they are new, but also because they complicate the perfusion methodology in clinical practice and, when used individually, only address AIF PVE error, obviating the need for the extra effort.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of CBF CC is simply then reflected in the variation of the control distribution. As an example, Sakaie et al (11) combined results from two previous PET studies and reported that normal WM CBF was 23.7 Ϯ 3.79 mL/minute/100 g (mean and standard deviation). Therefore, for normal subjects cross-calibrated to this normal WM CBF distribution, each voxel on the CBF CC map would have a relative standard error of 100% ⅐ 3.79/23.7 ϭ 16.0%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previously proposed Bookend method [7,8], CBV is estimated using steady-state measurements of T1 before and after contrast agent (CA) administration to determine the CF. The Bookend method has previously been compared to positron emission tomography (PET), which is commonly regarded as the gold standard method for CBF measurements, and a good correlation between the two methods was observed [9].…”
Section: Introductionmentioning
confidence: 99%